Heart Rate Recovery Index as a Functional Marker in Heart Failure with Preserved Ejection Fraction: Associations with H2FPEF Score, Longitudinal Systolic Function and Left Atrial Remodelling - Andreea Dache; Cristina Văcărescu; Minodora Teodoru; Mihai Octavian Negrea; Cristina Tudoran; Alexandra-Iulia Lazăr-Höcher; Liviu Cirin; Adelina Andreea Faur-Grigori; Bogdan-Simion Suciu; Dragoș Cozma (Journal of Clinical Medicine, 2026)
Background: The Heart Rate Recovery Index (HRRI), derived from post-exercise heart rate recovery (HRR), reflects autonomic function and cardiovascular performance. Whether HRRI reflects early myocardial dysfunction and left atrial remodelling in heart failure with preserved ejection fraction (HFpEF) has not been previously examined. The H2FPEF score, which integrates clinical and echocardiographic parameters, is used to assess the likelihood of HFpEF. This study investigates the relationship between HRRI, H2FPEF score, and echocardiographic markers of longitudinal systolic function, including mitral annular plane systolic excursion (MAPSE), as well as left atrial volume index (LAVI), in patients with preserved left ventricular ejection fraction. Methods: A prospective observational study included 241 patients referred for cardiac exercise testing at the Institute of Cardiovascular Diseases Timisoara and the Clinical County Hospital of Sibiu. HRRI was calculated as the ratio of heart rate acceleration time (AT) to deceleration time (DT) during exercise testing. A comprehensive echocardiographic assessment was performed on all patients. Statistical analysis involved univariate testing and multivariable logistic regression with stepwise selection. Results: HRRI was significantly lower in HFpEF patients compared with those without heart failure (1.97 ± 0.66 vs. 2.73 ± 1.08, p < 0.01). HRRI correlated significantly with exercise performance, age, H2FPEF score, and echocardiographic markers of diastolic and longitudinal systolic dysfunction. ROC analysis identified an HRRI cut-off value of 2.25 for HFpEF detection (AUC = 0.748), while HRRI remained significantly associated with HFpEF after adjustment for the covariates included in the model. The combined HRRI–H2FPEF score improved diagnostic discrimination compared with the H2FPEF score alone (AUC 0.897 vs. 0.858), achieving an overall classification accuracy of 82.2%. Conclusions: In our study, HRRI is significantly reduced in HFpEF and distinguishes patients with and without heart failure. It shows associations with echocardiographic markers of diastolic and longitudinal systolic dysfunction, exercise capacity, and H2FPEF score.